Open innovation in (young) SMEs. (February 2020) - Kraus, Sascha; Kailer, Norbert; Dorfer, Julia; Jones, Paul
The purpose of this article is to identify the role start-ups play in the open innovation (OI) context by reviewing the existing body of research. Since the OI literature on young ventures is nascent, a stepwise review approach is applied, using the already more evolved findings of small- and medium-sized enterprises (SMEs) in order to derive similarities or differences. The findings indicate that if empirical studies with a similar research focus are conducted, similar results are likely to be obtained in both SMEs and young ventures. Generally, young ventures have a higher application of OI activities compared to large firms as it boosts their innovation performance enabling them to overcome the liability of smallness and newness. Because of this importance, combined with the limited number of quantitative studies available, ongoing research is required to further understand young ventures role in the OI context.